KUALITAS PELAYANAN PROYEK OPERASI NASIONAL AGRARIA (PRONA) DI KECAMATAN MATTIRO SOMPE KABUPATEN PINRANG - Nurul Munia; Muhlis Madani; Abdi Abdi (Department of Public Administration, Muhammadiyah University of Makassar, 2018)
The purpose of this research is not only aimed to know the service quality but also to know the supporting and inhibiting factors of the public service in Prona. This research used qualitative research type which is choosen by certain sample who had knowledge about Prona Service Quality. The research result showed that 1) if the required file was completed then the certificate could be quickly resolved 2) the service flow could be said “good” 3) the employee had not done the best in their work 4) PRONA activites will be completed within one budget a year 5) public enthusiasm in enrolling their land by Prona 6) the less of surveyor staff become the most inhibiting factor of Prona service. Keywords: Quality, service, PRONA